Historical significance and current state of the "xiaokang society" creation in the People's Republic of China - Assyl, M.B.; Dauyen, D.B. (Journal of Oriental Studies, 2021)
Since Deng Xiaoping first introduced the concept of "xiaokang" in 1979, "creating a xiaokang (moderately prosperous) society" has been the main goal of Chinese leaders' modernization and reform efforts. The year of 2021 will be a special year in the history of the People's Republic of China on the road to "creating the xiaokang society". This year marks the 100th anniversary of the founding of the Communist Party, the completion of “creating the xiaokang society” and China's final victory over poverty. The article examines the theoretical aspect of the formation and practical application of the concept of "creating a xiaokang society", which is designated as the main goal of China's development over the past 40 years. Through an overview of the history of the concept formation, the place and role of the concept of "xiaokang" in the strategy of socio-economic development of China will be analyzed. Since it is considered as the main focus of the CPC Central Committee's work and an important stage in the process of China's socialist modernization, the study of the essence of the term "xiaokang" is particularly relevant. The concept "Xiaokang has undergone a three-stage transformation in the direction of implementing the party's policy: "General xiaokang society", "establishment of a comprehensive xiaokang society", and "completion of a comprehensive xiaokang society". The development of the state in this direction has brought great results to China and served as the basis for determining the future development strategy. Through creating the "xiaokang society", China expresses its desire for global leadership by acquiring wealth and power. Even the COVID-19 pandemic did not appease China, saying that the CPC will keep its promise.